Magnetothermal Properties near Quantum Criticality in the Itinerant Metamagnet Sr3Ru2O7 - Rost, Andreas W.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The compound Sr3Ru2O7 of the strontium ruthenate family has been intensely studied because experimental evidence suggests that quantum fluctuations dominate the magnetic phase diagram in the vicinity of a novel low-temperature phase. In order to understand the interplay between the quantum critical fluctuations and the phase formation, comprehensive thermodynamic information is essential. This thesis reports the results of both specific-heat and magnetocaloric experiments carried out with a bespoke experimental apparatus whose design particularly addresses the demanding constraints of the low-temperature, high-magnetic-field environment. The experimental data give evidence for unusual thermodynamic properties of the novel phase and its bounding phase transitions. Furthermore they show that the phase formation takes place against a background of strongly peaking entropy, suggesting that quantum criticality plays a key role in the physics of this system.
Background Physics -- Thermodynamic Measurements of Entropy -- Design and Characterisation of Novel Experimental Setup -- Experimental Results and Discussion -- Conclusions and Future Work -- Appendices.
Keywords: Physics; Magnetism; Physics; Magnetism, Magnetic Materials